Effects of somatic cell levels on milk components II-lactose and total solids - Prada e Silva, Luís Felipe; Pereira, Alfredo Ribeiro; Machado, Paulo Fernando; Sarriés, Gabriel Adrián (Brazilian Journal of Veterinary Research and Animal Science, 2000)
In laboratory, electronic determination of somatic cell count (SCC) and concentration of lactose and total solids of 1,361 milk samples were carried out in order to evaluate the effects of somatic cell count (SCC) on the concentrations of milk lactose and total solids. All the SCC data were transformed to a linear score. Increases in the SCC score were associated with decreased lactose concentration. This increase was highly significant (p < 0.0001), and about 34% of the lactose concentration variation could be accounted for variation of the SCC score. Total solids were not influenced by the SCC score.